(untitled) (Journal of Fatima Jinnah Medical University, 2020)
Background: Epilepsy is a common illness and most of the times it is diagnosed with standard electroencephalography (EEG). However, this is not positive in all the patients. Among these patients sleep deprived EEG is recommended by many authors but this is not routinely used. This study was conducted to evaluate that how commonly sleep deprived EEG will show positive results among patients with unspecified seizures having negative standard EEG. Patients and methods: This was a cross sectional survey that included 100 patients with unspecified seizure having negative standard EEG. All the patients had sleep deprived EEG. The frequency of patients positive for epilepsy on sleep deprived EEG was calculated. Results: Forty one (41%) patients were found positive for epilepsy on sleep derived EEG, while rest of 59 (59%) patients were negative. Conclusions: it is recommended that all the patients with unspecified seizures having negative standard EEG should have sleep deprived EEG in our clinical setup.